Sintered NdFeB magnetic powder molding release agent and high coercive force magnet preparation method
By using a mold release agent containing zinc stearate, epoxy resin, nano Cu and rare earth organic Dy(C5H5)3 during the molding process of sintered NdFeB magnet, the coercive force of sintered NdFeB magnet is solved by low at high temperatures. The problem of this method achieves the balance of high coercive force and high magnetic energy product, and simplifies the preparation process.
Patent Information
- Application Number
- CN202310889036.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-07-19
AI Technical Summary
The existing sintered NdFeB magnets have low coercivity at high temperatures, and although the addition of heavy rare earth elements can improve coercivity, it will reduce magnetic energy accumulation, and conventional diffusion processes consume high energy and are low in efficiency.
Using a sintered NdFeB magnetic powder molding release agent, including zinc stearate, epoxy resin, nano Cu and rare earth organic substance Dy(C5H5)3, the release agent is used to perform multifunctional treatment during the molding process, including Lubrication, antioxidant and diffusing agents to improve the coercivity of the magnet.
Without reducing the magnetic energy production, the coercive force of the sintered NdFeB magnet is significantly improved, the preparation process is simplified, the production cost is reduced, and the production efficiency is improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the field of permanent magnetic materials, and in particular relates to a sintered NdFeB magnetic powder molding release agent and a method for preparing a high coercive force magnet. Background Art
[0002] After nearly 40 years of development, the performance of sintered Nd-Fe-B magnets has been continuously improved. The experimental value of the maximum magnetic energy product (BH) max of the magnet has reached 59.6MGOe (474kJ / m-3), which is 93% of the theoretical limit (theoretical 64MGOe), and the experimental value of the remanence Br has also reached 1.55T, which is 97% of the theoretical value. There is limited room for further improving the remanence and magnetic energy product of the magnet, but the coercivity Hcj of the magnet is still low, which is 1 / 5 to 1 / 3 of the theoretical value. This greatly limits the application of sintered Nd-Fe-B magnets in many fields, especially in some high-temperature fields. High-performance sintered NdFeB permanent magnets with high temperature resistance are key components of high-power density permanent magnet drive motors. The drive motor has a high power density and a high operating temperature, which requires the rare earth permanent magnets used to maintain excellent magnetic properties at high temperatures, that is, the magnets must have high coercivity and high magnetic energy product at room temperature. However, the two key performance indicators, maximum magnetic energy product and intrinsic coercivity, are a pair of mutually restraining contradictions: the most effective way to increase the intrinsic coercivity is to add heavy rare earths Tb and Dy, but the addition of heavy rare earths will also significantly reduce the maximum magnetic energy product of the magnet. Therefore, the maximum magnetic energy product of NdFeB permanent magnets that can meet high temperature requirements is generally low.
[0003] The preparation process of sintered NdFeB involves a series of processes including batching, smelting, belt throwing, hydrogen cracking, powder making, mixing, molding, sintering and heat treatment. By improving the specific links of the above process, it is expected that the coercive force of the magnet will be improved without significantly reducing the maximum magnetic energy product of the material. In order to improve the utilization efficiency of heavy rare earth Dy / Tb and avoid the antiferromagnetic coupling between Dy / Tb and Fe atoms, a process method for grain boundary diffusion of heavy rare earth elements has been proposed. This process is different from the direct smelting and addition of heavy rare earth elements to alloys. It is to coat and plate the surface of the dense magnet after sintering with heavy rare earth Dy and Tb diffusion sources. During the high-temperature sintering process, due to the difference in element concentration gradient, the added heavy rare earth elements Dy / Tb will diffuse into the grain boundary layer of the Nd-Fe-B main phase, replacing the original Nd on the grain boundary of the main phase to form (Nd, Dy) 2 Fe 14 B / (Nd,Tb) 2 Fe 14B hard magnetic shell phase, the effective magnetocrystalline anisotropy field of the epitaxial layer of the main phase grains is greatly improved, the reverse magnetization nucleation is suppressed, and the coercive force of the magnet can be effectively improved without significantly reducing the remanence and magnetic energy product. Due to the element diffusion process, only a small amount of heavy rare earth elements enter the outer boundary of the 2:14:1 main phase grains. The core of the main phase grains is a 2:14:1 hard magnetic phase without heavy rare earth Dy / Tb, or with a very low Dy / Tb content, which effectively curbs the antiferromagnetic coupling between heavy rare earth Dy / Tb and Fe atoms, ensuring the remanence and magnetic energy product of the magnet.
[0004] The surface of the dense magnet after sintering is coated with heavy rare earth Dy and Tb diffusion sources, and then a subsequent high-temperature heat treatment is performed for diffusion. The surface local magnetic anisotropy field can be increased, and the coercive force can be increased. For example, patent CN108122654A discloses a method for preparing a grain boundary diffused heavy rare earth NdFeB magnetic material, in which heavy rare earth elements are evaporated on the surface of the sintered magnet, and then diffused and infiltrated for 7 hours. This process can effectively improve the coercive force of the magnet, but because the heavy rare earth elements are diffused on the surface of the dense magnet after sintering, there are few diffusion channels, a small diffusion depth, and a slow diffusion process, so the energy consumption is very high and the efficiency is extremely low. Summary of the invention
[0005] The purpose of the present invention is to provide a sintered NdFeB magnetic powder molding release agent and a method for preparing a high coercive force magnet, so as to overcome the problems in the prior art of high-temperature-resistant high-coercive force NdFeB magnets, such as high oxygen content, low coercive force, complex conventional heavy rare earth grain boundary addition process, high energy consumption for heavy rare earth diffusion, and low production efficiency.
[0006] The technical solution to achieve the purpose of the present invention is: a sintered NdFeB magnetic powder molding release agent, including zinc stearate, epoxy resin, nano Cu and rare earth organic matter Dy (C 5 H 5 ) 3 ; The solvent of the release agent is gasoline.
[0007] Furthermore, the specific composition of each component in the release agent is as follows: 1.0-5.0wt.% zinc stearate, 0.5-2.0wt.% epoxy resin, 0.5-2.0wt.% nano Cu, 1.0-10.0wt.% rare earth organic Dy(C 5 H 5 ) 3 ; The balance is gasoline solvent.
[0008] Furthermore, the average particle diameter of the nano-Cu is 50-100 nm.
[0009] A method for preparing a high coercive force magnet using the above-mentioned release agent comprises the following steps:
[0010] Step (1): Prepare a granular material with an average particle size of 3.5±0.5 μm and a composition of (Pr 0.2 Nd 0.8 ) 30.5 Fe 67 M 1.5 B 1.0 Powder, wherein M is other trace elements;
[0011] Step (2): coating the mold release agent according to any one of claims 1 to 3 on the inner wall of the mold and the surfaces of the upper and lower pressure heads, loading the powder prepared in step (1), performing orientation pressing in a magnetic field of 1.2±0.2T, and then performing cold isostatic pressing at 200±20MPa, and demolding to obtain a non-dense green body;
[0012] Step (3): spraying the release agent according to any one of claims 1 to 3 on the surface of the non-dense green body prepared in step (2);
[0013] Step (4): vacuum sintering and heat treatment to obtain a high coercive force Nd-Fe-B magnet.
[0014] Furthermore, in step (2), the release agent coated on the inner wall of the mold and the upper and lower pressure head surfaces has a spraying pressure of 0.8 MPa, a nozzle distance of 10 to 15 cm, and a spraying time of 0.5 to 1.0 s;
[0015] In step (3), the release agent is sprayed at a spraying pressure of 0.8 to 1.0 MPa, a nozzle distance of 10 to 15 cm, and a nozzle speed of 3 to 5 cm / s.
[0016] Furthermore, the process parameters of the vacuum sintering in step (4) are specifically: sintering at 1065° C. for 3±0.2 h, and then tempering at 890° C. for 4.5±0.5 h.
[0017] A high coercive force NdFeB magnet is prepared by the above method.
[0018] Compared with the prior art, the present invention has the following significant advantages:
[0019] (1) The present invention innovatively designs a new multifunctional release agent for magnetic powder molding, which gets rid of the limitation of traditional release agents that only have lubrication and demolding functions. Through the optimized design of multiple components such as lubrication, antioxidant, diffusant, solvent, etc., the simplified preparation of low-oxygen-content, high-coercive-force sintered NdFeB magnets is achieved without changing the original production process.
[0020] (2) The coercive force of NdFeB depends on the intrinsic magnetocrystalline anisotropy of the material. Adding heavy rare earth Dy can effectively improve the magnetic anisotropy and the coercive force. However, since the atomic magnetic moment of Dy and the atomic magnetic moment of Fe are arranged in antiparallel, the magnetic moments cancel each other out. Adding heavy rare earth Dy will reduce the remanence of the material. In fact, the coercive force of NdFeB is mainly controlled by the demagnetization process of the surface layer of the magnet. Therefore, the magnetocrystalline anisotropy field of the surface layer of the magnet can be effectively improved by diffusing heavy rare earth on the surface layer. The present invention adds fluid Dy (C 5 H 5 ) 3 The organic heavy rare earth diffusion source improves other diffusion processes on the surface of dense magnets that have been sintered. There is no need for long-term heat treatment diffusion on the surface of the sintered magnets, which greatly shortens the preparation process and improves production efficiency.
[0021] (3) Abandoning the previous use of micron-sized heavy rare earth hydrides (TbH, DyH), heavy rare earth metals / alloys (Dy, Tb, DyNiAl) and other additives such as heavy rare earth element diffusion sources, the present invention uses heavy rare earth Dy (C 5 H 5 ) 3 The combination of organic solvents and their surface addition when coating the release agent solves the problems of poor dispersibility and uneven distribution of large-size powder diffusion sources and complex heavy rare earth surface coating diffusion process.
[0022] (4) The size of NdFeB molding magnetic powder is small (~3μm), and it is very easy to oxidize and fail (due to the extremely active chemical properties of rare earth, it will burn when it encounters air). The molded green body will pass through the magnetic field press to the converter process of the sintering furnace. The active magnetic powder on the surface of the green body will inevitably contact the air and cause surface oxidation. When the present invention is demolded during molding, the surface of the green body is covered with the antioxidant release agent, which effectively inhibits the oxygen control of the non-dense molded green body in the converter process and reduces the thickness of the oxide layer on the surface of the green body after molding.
[0023] (5) Nano-sized Cu is used as an active combined diffusion source, which can react with the Nd-rich rare earth phase at the NdFeB grain boundary to form a low melting point (PrNd)-Cu grain boundary phase, which can not only broaden the diffusion channel but also improve the heavy rare earth source Dy (C 5 H 5 ) 3 The diffusion efficiency of Dy in the magnet can be improved. At the same time, due to the better ductility and electrochemical corrosion potential of Cu, it can play a role in toughening and corrosion resistance of the magnet surface. In addition, considering the addition of nano-metals and rare earth organics in this release agent, epoxy resin is an indispensable component to improve the powder formability. DETAILED DESCRIPTION
[0024] The present invention is described in further detail below.
[0025] The present invention optimizes and modifies the magnetic powder molding process. Different from the above-mentioned cumbersome additional method of mixing multiple powders and coating the surface after sintering, a sintered NdFeB magnetic powder molding release agent and a method for preparing a high coercive force magnet are proposed. The release agent is used for coating the inner wall of the mold in the powder magnetic field orientation molding process, which is convenient for magnetic powder orientation and demolding. At the same time, the release agent ingredients include antioxidant, corrosion protection and coercive force enhancement and other gain effects. The existing release agents are all designed with consideration of magnet molding lubrication and demolding integrity in component formula design. The release agent proposed in the present invention comprehensively considers magnet molding lubrication and diffusion multifunctionality. At the same time, in the actual magnet preparation process, there is no need for mixing, no need to change the existing production process, and no need for additional long-term heat treatment. Therefore, the process is simple and the energy consumption is low. While maintaining a high magnetic energy product, the coercive force of the Nd-Fe-B sintered magnet is successfully increased to more than 20kOe. The method is suitable for large-scale production.
[0026] The present invention adopts the modification of high-efficiency composite release agent and the optimization of the preparation process of sintered magnet to realize the preparation of high magnetic energy product and high coercive force NdFeB magnet, which is specifically realized by the following technical scheme:
[0027] The composite molding release agent designed by the present invention at least comprises the following components: 1.0-5.0wt.% zinc stearate, 0.5-2.0wt.% nano Cu, 0.1-10.0wt.% Dy(C 5 H 5 ) 3 and 0.5-2.0wt% of epoxy resin.
[0028] The present invention also provides a method for preparing a sintered NdFeB magnet with high coercivity and high magnetic energy product, the main steps of which are:
[0029] Step 1, preparing Nd-Fe-B alloy rapid quenching thin strip by induction melting and rapid solidification casting process;
[0030] Step 2, crushing the thin strip obtained in step 1 into alloy powder by hydrogen crushing and air flow milling;
[0031] Step 3, coating the inner wall and upper and lower pressure heads of the magnetic field forming mold with the composite release agent;
[0032] Step 4: Fill the alloy powder of step 2 into a mold for orientation pressing, and perform cold isostatic pressing on the pressed magnetic block to obtain a non-completely dense green body.
[0033] Step 5, spraying the composite release agent on the surface of the non-completely dense raw material after cold isostatic pressing in step 4 again;
[0034] Step 6: subjecting the green body in step 5 to high temperature sintering and heat treatment to obtain a high coercive force sintered magnet.
[0035] Example 1
[0036] A composite release agent for sintered NdFeB magnetic powder molding, the main components of which are 3.0wt.% zinc stearate, 0.5wt.% nano Cu (d~50nm), 2.0wt.% Dy (C 5 H 5 ) 3 , 0.5wt% epoxy resin, the balance is 95# gasoline;
[0037] The application of the composite release agent in the preparation of high coercive force magnets includes the following steps:
[0038] Step 1: Prepare alloy powder by induction melting, rapid solidification casting, hydrogen crushing and air flow milling of Nd-Fe-B alloy, the average particle size of the powder is 3.5 μm, and the composition of the alloy is (Pr 0.2 Nd 0.8 ) 30.5 Fe 67 M 1.5 B 1.0 , where M is other trace elements;
[0039] Step 2: spray the composite release agent on the inner wall and upper and lower pressure heads of the mold with a spraying pressure of 0.8 MPa, a nozzle distance of 10 cm, and a spraying time of 0.5 s. Then, the obtained alloy magnetic powder is oriented and pressed under a magnetic field of ~1.2 T; the pressed magnetic block is cold isostatically pressed at ~200 MPa to form a non-dense green body.
[0040] Step 3: spray the composite release agent on the surface of the non-completely dense raw material after cold isostatic pressing again, with the spraying air pressure of 0.8Mpa, the nozzle distance of 15cm, and the nozzle speed of 5cm / s.
[0041] Step 4: Sinter at 1065° C. for 2.5 h in a vacuum sintering furnace, and then temper at 890° C. for 4 h to finally obtain a Nd-Fe-B sintered magnet.
[0042] Example 2
[0043] A composite release agent for sintered NdFeB magnetic powder molding, the main components of which are 3.0wt% zinc stearate, 0.5wt% nano Cu (d~50nm), 5.0wt% Dy (C 5 H 5 ) 3 , 0.5wt% epoxy resin, the balance is 95# gasoline;
[0044] The application of the composite release agent in the preparation of high coercive force magnets includes the following steps:
[0045] Step 1: Prepare alloy powder by induction melting, rapid solidification casting, hydrogen crushing and air flow milling of Nd-Fe-B alloy, the average particle size of the powder is 3.5 μm, and the composition of the alloy is (Pr 0.2 Nd 0.8 ) 30.5 Fe 67 M 1.5 B 1.0 , where M is other trace elements;
[0046] Step 2: spray the composite release agent on the inner wall and upper and lower pressure heads of the mold with a spraying pressure of 0.8 MPa, a nozzle distance of 10 cm, and a spraying time of 0.5 s. Then, the obtained alloy magnetic powder is oriented and pressed under a magnetic field of ~1.2 T; the pressed magnetic block is cold isostatically pressed at ~200 MPa to form a non-dense green body.
[0047] Step 3: spray the composite release agent on the surface of the non-completely dense raw material after cold isostatic pressing again, with the spraying air pressure of 0.8Mpa, the nozzle distance of 15cm, and the nozzle speed of 5cm / s.
[0048] Step 4: Sinter at 1065° C. for 3 h in a vacuum sintering furnace, and then temper at 890° C. for 4.5 h to finally obtain a Nd-Fe-B sintered magnet.
[0049] Example 3 A composite release agent for sintered NdFeB magnetic powder molding, the main components of which are 5.0 wt.% zinc stearate, 0.5 wt.% nano Cu (d ~ 50 nm), 2.0 wt.% Dy (C 5 H 5 ) 3 , 0.5 wt% epoxy resin, the balance is 95# gasoline; the application of the composite release agent in the preparation of high coercive force magnets comprises the following steps:
[0050] Step 1: Prepare alloy powder by induction melting, rapid solidification casting, hydrogen crushing and air flow milling of Nd-Fe-B alloy, the average particle size of the powder is 3.5 μm, and the composition of the alloy is (Pr 0.2 Nd 0.8 ) 30.5 Fe 67 M 1.5 B 1.0 , where M is other trace elements;
[0051] Step 2: spray the composite release agent on the inner wall and upper and lower pressure heads of the mold with a spraying pressure of 0.8 MPa, a nozzle distance of 10 cm, and a spraying time of 0.5 s. Then, the obtained alloy magnetic powder is oriented and pressed under a magnetic field of ~1.2 T; the pressed magnetic block is cold isostatically pressed at ~200 MPa to form a non-dense green body.
[0052] Step 3: spray the composite release agent on the surface of the non-completely dense raw material after cold isostatic pressing again, with the spraying air pressure of 0.8Mpa, the nozzle distance of 15cm, and the nozzle speed of 2cm / s.
[0053] Step 4: Sinter at 1065° C. for 3 h in a vacuum sintering furnace, and then temper at 890° C. for 4.5 h to finally obtain a Nd-Fe-B sintered magnet.
[0054] In order to facilitate comparison, the same magnetic powder formula (Pr 0.2 Nd 0.8 ) 30.5 Fe 67 M 1.5 B 1.0 , conventional mold release agent (zinc stearate + petroleum ether), the same molding and sintering preparation process to obtain comparative magnet 1#. The prepared sintered NdFeB magnet comparative magnet 1#, Example 1#, Example 2# and Example 3# were put into a BH loop tester to measure their various magnetic performance indicators along the orientation direction, and the statistics are as follows Table 1:
[0055] As shown in Table 1, the composite release agent can effectively maintain the orientation of magnetic powder, and the orientation degree and the remanence of the magnet do not change significantly. However, the coercive force of the magnet can be significantly improved. The oxygen content of the magnet is significantly reduced after sintering, which is mainly due to the oxidation control of the green body surface and the contribution of the nano and organic diffusion sources in the composite release agent. The above specific examples are examples of some of the better results of the present invention, but the present invention is not limited to the above embodiments.
Claims
1. A sintered NdFeB magnetic powder molding release agent, characterized in that: It includes zinc stearate, epoxy resin, nano Cu and rare earth organic matter Dy(C5H5)3; the solvent of the release agent is gasoline; The specific composition of each component in the release agent is as follows: 1.0-5.0wt.% of zinc stearate, 0.5-2.0wt.% of epoxy resin, 0.5-2.0wt.% of nano Cu, 1.0-10.0wt.% of rare earth organic matter Dy(C5H5)3; the balance is gasoline solvent.
2. The release agent according to claim 1, characterized in that The average particle diameter of nano Cu is 50-100 nm.
3. A method for preparing a high coercive force magnet using the release agent according to any one of claims 1 to 2, characterized in that: The steps include: Step (1): Prepare a granular material with an average particle size of 3.5±0.5 μm and a composition of (Pr 0.2 Nd 0.8 ) 30.5 Fe 67 M 1.5 B 1.0 Powder, wherein M is other trace elements; Step (2): coating the mold release agent according to any one of claims 1 to 3 on the inner wall of the mold and the surfaces of the upper and lower pressure heads, loading the powder prepared in step (1), performing orientation pressing in a magnetic field of 1.2±0.2T, and then performing cold isostatic pressing at 200±20MPa, and demolding to obtain a non-dense green body; Step (3): spraying the release agent according to any one of claims 1 to 3 on the surface of the non-dense green body prepared in step (2); Step (4): vacuum sintering and heat treatment to obtain a high coercive force Nd-Fe-B magnet.
4. The method according to claim 3, characterized in that In step (2), the release agent coated on the inner wall of the mold and the upper and lower pressure heads has a spraying pressure of 0.8 MPa, a nozzle distance of 10 to 15 cm, and a spraying time of 0.5 to 1.0 s; In step (3), the release agent is sprayed at a spraying pressure of 0.8 to 1.0 MPa, a nozzle distance of 10 to 15 cm, and a nozzle speed of 3 to 5 cm / s.
5. The method according to claim 4, characterized in that The specific process parameters of vacuum sintering in step (4) are: sintering at 1065° C. for 3±0.2 h, and then tempering at 890° C. for 4.5±0.5 h.
6. A high coercivity NdFeB magnet, characterized in that: The method is prepared by any one of claims 3 to 5.
Citation Information
Patent Citations
Grain-boundary-diffusion heavy rare earth and neodymium iron boron magnetic material and preparation method thereof
CN108122654A
Antisticking agent for sintering and molding neodymium iron boron
CN101406927A
Releasing agent and preparation method thereof
CN102085563A